Protective immune response against newly emerging goose tembusu virus infection induced by immunization with a recombinant envelope protein. (1st October 2015) - Zhao, D.; Huang, X.; Han, K.; Liu, Y.; Yang, J.; Liu, Q.; An, F.; Li, Y.
Abstract: Flavivirus envelope protein locates at the outermost surface of viral particle and mediates virus entry and fusion infection, and plays an important role in eliciting neutralizing antibody. In this study, goose tembusu virus (GTV) E protein was expressed and purified from Escherichia coli . The immunological changes and protection efficiency of this protein serving as recombinant subunit vaccine were then tested. In ducks, recombinant E protein markedly elicited specific neutralizing antibody, stimulated the secretion of IL‐2, TNF‐ α and IFN‐γ cytokines and promoted the proliferation of lymphocytes. Additionally, population of soluble CD4 and soluble CD8 molecules in sera significantly increased in response to this antigen. Moreover, virus challenge revealed that recombinant E protein contributed to protection against GTV challenge. Taken together, the data indicate that recombinant GTV E protein could induce significant humoral and cell‐mediated responses and that recombinant E protein can serve as a potential subunit vaccine candidate against GTV. Significance and Impact of the Study: The sudden outbreak and quick spread of newly emerging goose tembusu virus (GTV) have resulted in serious economic loss. There is no effective commercial vaccine or reasonably available control measure so far. In this study, GTV E protein was expressed and purified from Escherichia coli, and it was found that recombinant E protein could induce significant humoral and cell‐mediated responses. It indicated that recombinant E protein can serve as a potential subunit vaccine candidate against GTV.